Evaluation of three types of dentin surface treatments on the shear bond strength of two composite resin restorations. - in vitro study - - Redhwan Abdullah Al-aslami; Haithem J Al-Azzawi
The purpose of this study was to assess the effect of 3 dentin surface treatments (1) acidetch, (2) air abrasion and (3) combination of acid etch + air abrasion), on the shear bond strength of two different types of adhesive system (Septodent/Syntac Sprint). Also, the dentin surface roughness resulting from the use of these 3 types of dentin surface treatment was evaluated. Eight five extracted 1st and 2nd human mandibular teeth were used in this study in which the crowns were sectioned at the cementoenamel junction and embedded in acrylic resin leaving the buccal surface exposed. A flat dentin surface was obtained by grinding with 60-grit silicon carbid abrasive paper followed by 600 grit silicon carbid abrasive paper with water. The samples were divided randomly into 3 groups: Group I: 14 samples were treated with acid etching only, and further subdivided into two equal subgroups according to the type of adhesive system used. Group II: 28 samples were treated with air-abrasion only and further subdivided into four equal subgroups according to the different types of adhesive systems and also to the different time of exposure to the air abrasive particles. Group III: 28 samples were treated with combination of air-abrasion and acid etching and further subdivided into four equal subgroups according to the type of adhesive system and to the time of exposure to the air-abrasive particles. The remaining 15 samples were used to determine the surface roughness resulted from the use of 3 different types of dentin surface treatment. The results of this study showed that the highest shear bond strengths were obtained with use of combination of (air abrasion and acid etching) followed by (acid etching), (air abrasion) respectively. Also the results of this study indicated that increasing the surface roughness did not have a direct effect on shear bond strength, but it increased the surface area available for bonding.